2011
DOI: 10.1039/c1cc13615a
|View full text |Cite
|
Sign up to set email alerts
|

A water soluble vitamin B12-Re(i) fluorescent conjugate for cell uptake screens: use in the confirmation of cubilin in the lung cancer line A549

Abstract: A water soluble vitamin B(12)-rhenium conjugate was synthesized and used in concert with intrinsic factor to screen for cubilin receptor-mediated uptake in lung cancer cells. Internalization of the conjugate demonstrated that it could be used to rapidly screen for the cubilin receptor in living cells, subsequently confirmed with Western blotting and RT-PCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 20 publications
0
46
0
Order By: Relevance
“…For example, cubilin 146 , which is mainly localized in the kidney, is involved in the excretion of CC16 147 . Cubilin is also expressed by lung epithelial cells and contributes to high-density lipoprotein uptake by alveolar epithelium 148 and lung cancer cells 149 . CC16 was recently identified as a ligand of the lipocalin-1 receptor, and CC16 binding to lipocalin-1 reduces the migration and invasion of carcinoma cells in vitro 150 .…”
Section: Club Cell Protein-16 (Cc16)mentioning
confidence: 99%
“…For example, cubilin 146 , which is mainly localized in the kidney, is involved in the excretion of CC16 147 . Cubilin is also expressed by lung epithelial cells and contributes to high-density lipoprotein uptake by alveolar epithelium 148 and lung cancer cells 149 . CC16 was recently identified as a ligand of the lipocalin-1 receptor, and CC16 binding to lipocalin-1 reduces the migration and invasion of carcinoma cells in vitro 150 .…”
Section: Club Cell Protein-16 (Cc16)mentioning
confidence: 99%
“…152 This time, a photoactivatable Mn-containing CORM (structure not shown) was attached to the 5`-OH moiety of the vitamin B 12 scaffold. 146,147,151,165,166 Figure 8 shows one example from the Grissom group, a Cbl-rhodamine conjugate (7). 153 Modifications at the 5`-OH moiety of Cbls have also been explored for the development of luminescent probes.…”
Section: Vitamin B 12 Derivatives For Diagnosis and Therapymentioning
confidence: 99%
“…146,147,151,165,166 Figure 8 shows one example from the Grissom group, a Cbl-rhodamine conjugate (7). 145,146 146,147,151 Studying the interactions between Cbls and proteins, Fedosov and co-workers developed an elegant kinetic method for determining the high binding constants of Cbl@protein complexes using fluorescent Cbl-conjugates. 146 This particular design was chosen to minimise undesired contact quenching of fluorescence by interactions of the fluorophore with the corrin-macrocycle.…”
Section: Vitamin B 12 Derivatives For Diagnosis and Therapymentioning
confidence: 99%
“…[87] Although the fluorescence of the isolated conjugate was very weak (owing to quenching induced by the bound vitamin B 12 ), upon addition of IF a more than 15-fold increase in fluorescence intensity was observed with a concomitant blue shift (ca. 30 nm) in the emission maximum.…”
Section: Rheniummentioning
confidence: 99%
“…They reported on some fluorescent water-soluble vitamin B 12 -{Re I (CO) 3 } conjugates ( Figure 15) capable of probing cancer cells. [86,87] Again, the {Re I (CO) 3 } moiety was attached to the 5′-hydroxy position The targeted delivery of 25 to the cubilin receptor was successfully demonstrated; in fact, it was observed that it requires IF and exploits the IF-cubilin import mechanism. Confocal microscopy results showed internalization and accumulation of 25 bound to IF in the nuclear and cytosolic region of the cubilinoverexpressing human placental choriocarcinoma BeWo cells.…”
Section: Rheniummentioning
confidence: 99%